Electromagnetic Interference Shielding Effectiveness of Natural and Chlorobutyl Rubber Blend Nanocomposite - Tomy Muringayil Joseph (17542053) (2022)
The science and technology of electrical equipment for communication experience a rapid growth rate. However, the unwanted interference of electromagnetic waves of different electronic devices brought serious anxiety about human health as well as the lifetime and performance of the systems. To combat these consequences, we need to lessen the electromagnetic wave emission by making our devices more noise-sensitive. Herein, we incorporated carbon nanotubes (CNTs) at different ratios into natural rubber (NR) and chlorobutyl rubber (CIIR) to achieve shielding efficiency, along with carbon nanofibers (CNFs), nanoclay (NC), and carbon black (CB) to manipulate EMI shielding performance. The blend of CIIR/NR in a 70/30 (w/w) ratio also mixed with CNT, CNF, CB and NC. The effect of different fillers and their concentration/combination was analyzed by UV spectroscopy, demonstrating an absorbance peak in CIIR in 320 nm. From FTIR spectroscopy, it was evident that CIIR/CNT (5 phr), NR (30 wt.%)/CIIR (70 wt.%)/CB (5 phr), and NR (30 wt.%)/CIIR (70 wt.%)/CNT (5 phr) new bonding signatures were detected. The dielectric spectroscopic analyses were reflected in dielectric loss, dielectric permittivity and AC conductivity, where NR (30 wt.%)/CIIR (70 wt.%)/CB (5 phr) blend nanocomposite with 5 dB showed significantly higher EMI shielding performance compared to CIIR/CNT (5 phr) and CIIR/CNF (5 phr) with 29 and 15 dB, respectively. The greater the concentration of nanofiller, the lower the electromagnetic interference (EMI) shielding, i.e., CIIR/CNT (10 phr) with 15 dB (≈−48% dB), but with more agglomeration. Surprisingly, even a combination of fillers did not lead to higher EMI performance, such that CIIR/CNT (5 phr)-CB (20 phr) showed an EMI shielding value of 59 dB. Other Information Published in: Journal of Composites Science License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/jcs6080240 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.